Agile Testing Automation Framework (International Journal of Engineering and Computer Science, 2016)
Software testing is one of the most important phases of Software Development Life Cycle and main technique to find bugs and ensure the quality of the software. Software Testing can be conducted manually as well as automated. In manual testing, testing is done without any tool. In automation testing, testing is done with the help of automated testing tools. In recent times, agile development and testing are growing in popularity. Agile testing tools vary from project management tools to automated testing tools. In this paper, we have explained the detailed working of Agile Testing Framework (ATF). The ATF is about implementing the ideal automated testing environment in an agile organization, to deliver quality software, fast. The ATF Architecture can be used to easily integrate with continuous integration tools and best in class third-party testing tools to allow for accessibility, security, web consistency and full performance (front-end, middleware and load) testing.